2002
DOI: 10.1095/biolreprod.102.004648
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Estradiol on NADPH Diaphorase/Neuronal Nitric Oxide Synthase Activity and Colocalization with Progesterone or Type II Glucocorticoid Receptors in Ovine Hypothalamus1

Abstract: Nitric oxide (NO) has been shown to play an important role in both the neuroendocrine reproductive and stress axes, which are closely linked. Because progesterone (P 4 ) receptors (PRs) and glucocorticoid receptors (GRs) are not found in GnRH neurons and the NOergic system has been implicated in the control of GnRH secretion, this study aimed to ascertain whether steroids altered the NOergic system. Our first objective was to map the distribution of NO synthase (NOS) cells in the ovine preoptic area (POA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
4
12
0
Order By: Relevance
“…Indeed, LH and FSH secretion from the pituitary of handled rats can reach amounts that are not different from nonhandled ones, provided that plasma levels of estradiol and progesterone have been restored. Previous studies have shown that NOS synthesis is estradiol-dependent and estradiol receptors have been detected in the NOergic neurons in the MPOA [54,55,56]. Since neonatally handled female rats show low levels of estradiol during proestrus [12], we may speculate that this reduction could decrease NOS expression and, as a consequence, the NO activity in the MPOA would also be reduced in that particular phase of the estrous cycle.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, LH and FSH secretion from the pituitary of handled rats can reach amounts that are not different from nonhandled ones, provided that plasma levels of estradiol and progesterone have been restored. Previous studies have shown that NOS synthesis is estradiol-dependent and estradiol receptors have been detected in the NOergic neurons in the MPOA [54,55,56]. Since neonatally handled female rats show low levels of estradiol during proestrus [12], we may speculate that this reduction could decrease NOS expression and, as a consequence, the NO activity in the MPOA would also be reduced in that particular phase of the estrous cycle.…”
Section: Discussionmentioning
confidence: 87%
“…A variety of stressors dramatically inhibit GnRH and LH secretion (Smith et al 2003, Goodman & Inskeep 2006 in adult ewes, and stressors such as high temperature might act to inhibit LH at some times and not others. Although NOS is stimulated by stress in rats (Kishimoto et al 1996, Kim & Rivier 2000, we know of no evidence directly linking NO to stress-induced inhibition of LH secretion in sheep, however, recently, glucocorticoid receptors have been found to colocalise with NADPH diaphorase-positive neurones in the preoptic area, arcuate nucleus and ventromedial nucleus of the ewe (Dufourny & Skinner 2002). The high degree of coexistence between NADPHd/NOS activity and the expression of glucocorticoid receptors in sheep suggests a direct control of NO production by corticosteroids and a possible mechanism by which glucocorticoids may inhibit GnRH secretion (Dufourny & Skinner 2002).…”
Section: Discussionmentioning
confidence: 97%
“…One neurotransmitter that may be produced by these cells and inhibit GnRH release is NO. In the sheep, a subset of oestrogenresponsive neurones within the POA contains NOS (Dufourny & Skinner 2002) and this neurotransmitter has been implicated in the feedback actions of oestrogen in the rat (Brann & Mahesh 1997, Herbison 1998) and other species (Honaramooz et al 1999). Our studies tested the hypothesis that actions of NO are important in the vmPOA for the inhibition of LH secretion that occurs during seasonal anoestrus using local administration of drugs that block the synthesis of NO by inhibiting NOS or neural NOS (nNOS).…”
Section: Introductionmentioning
confidence: 99%
“…The neurochemical identity of these multi-receptive cells remains to be determined, as well as, the networks that these cells establish with others cell populations involved in reproduction such as GnRH neurons. One neurotransmitter that could be involved is nitric oxide (NO), since we recently found [40]that a high percentage of NO-producing neurons contained PR and GR in the POA (80%) and ARC (85%), and PR in the VMNvl (89%). It is therefore reasonable to assume that a subpopulation of these NOergic neurons may also be thyroid hormone receptive.…”
Section: Discussionmentioning
confidence: 99%